Robert Estienne, royal printer an historical study of the elder Stephanus - Armstrong, Elizabeth 1917-2001 (Cambridge University Press, 2011)
"This book was originally published in 1954. Robert Estienne was born in Paris in the early years of the sixteenth century, the son of a successful printer-bookseller. He became a printer himself, and one distinguished not only for the quality of his printing, but also for his scholarship. He was the most outstanding figure of the Parisian book trade at the moment when that trade was one of the most important agencies of the various intellectual movements which we summarize as 'The Renaissance'. Estienne was not only a classical but also a biblical scholar and editor (he is remembered as much for his editions of the Bible as for the beauty of his Cicero or for his use of the Garamond Greek types). Mrs Armstrong gives a full-length historical study of an important and admirable figure."--Book description, Amazon.com
Reprint of the original 1954 edition
Keywords: Estienne, Robert -- 1503-1559; Estienne, Robert / 1503?-1559; Estienne family; Printing / France / History / 16th century; Printing / Switzerland / History / 16th century; Printers / France / Biography; Printers / Switzerland / Biography; France / Imprints; Switzerland / Imprints; Printers; Printing; France; Switzerland; 1500-1599; Bibliography; Biography; History